2018
DOI: 10.4314/evj.v22i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ixodid ticks infesting Raya cattle breeds in Semi-arid areas of Raya Azebo district, northern Ethiopia

Abstract: A cross-sectional study was conducted from January to December, 2016 in Semi-arid areas of Raya Azebo District with the objectives to estimate the prevalence of ixodid ticks and assessing the difference in infestation among the different host risk factors such as age, sex and body condition scores. A total of 2697 adult ixodid ticks were collected from 488 Raya cattle breed selected randomly. Tick species were identified morphologically and the prevalence of the infested animals was estimated in relation to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(17 reference statements)
0
4
1
Order By: Relevance
“…Tick infestation was most common in animals in good body condition (75.00%) and least common in animals in poor body condition (72.93%). This finding is inconsistent with the findings of ( Gedilu et al, 2014 ) in and around Bahirdar, and ( Hadgu et al, 2018 ) in the Raya Asebo district. This could be because poorly conditioned animals were the least resistant to tick infestations and lacked the body potential to build resistance, whereas well-conditioned animals fought the infestation effectively ( Manan et al, 2007 ).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Tick infestation was most common in animals in good body condition (75.00%) and least common in animals in poor body condition (72.93%). This finding is inconsistent with the findings of ( Gedilu et al, 2014 ) in and around Bahirdar, and ( Hadgu et al, 2018 ) in the Raya Asebo district. This could be because poorly conditioned animals were the least resistant to tick infestations and lacked the body potential to build resistance, whereas well-conditioned animals fought the infestation effectively ( Manan et al, 2007 ).…”
Section: Discussioncontrasting
confidence: 97%
“…Ticks feed on blood, cause skin and hide damage, secrete toxins, and put cattle at risk of myiasis and dermatophilosis. Furthermore, they create areas for secondary pathogen invasion and reduce body weight growth and milk output ( Hadgu et al, 2018 ). Ticks also spread diseases from sick cattle to healthy cattle.…”
Section: Introductionmentioning
confidence: 99%
“…This has also been justified from the data obtained from the national meteorological agency of Ethiopia. The increased weight loss and weakness of animals reported by the smallholder farmers could also be associated with tick infestations that are predominant in the study areas (Hadgu et al , 2018). The higher mean mortality in sheep and cattle could be because of the grazing nature of these animals which could facilitate transmission of soilborne diseases and shortage of grazing land (Thornton et al , 2009).…”
Section: Discussionmentioning
confidence: 96%
“…This study was based on the presence and occurrence points of the ixodid ticks of cattle breeds in the semiarid areas of Raya Azebo. Tick presence data was checked from the previous research conducted in the same study area by Hadgu et al (2018). According to this study report, out of the 90% tick prevalence reported, six tick species that belong to the genera of Rhipicephalus (54%), Boophilus (5%), Amblyomma (3%), and Hyalomma (2.7%) were identified and the most dominant tick genus Rhipicephalus (54%) was taken as the study target in the present study.…”
Section: Data Types Sources and Analysis Approach Tick Presence Datamentioning
confidence: 99%